2013
DOI: 10.1002/acp.2983
|View full text |Cite
|
Sign up to set email alerts
|

Order and Strength Matter for Evaluation of Alibi and Eyewitness Evidence

Abstract: We explored the effects of presentation order and evidence strength on participants acting as investigators in a criminal context. Participants evaluated evidence and suspect guilt in a study in which alibi witness and eyewitness evidence of varying strength, presented in different orders, were compared. In contrast to research on the confirmation bias, which suggests that evidence presented early distorts subsequent evaluations of evidence, the present findings suggest that under certain circumstances, eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
33
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 52 publications
7
33
3
Order By: Relevance
“…Note, however, that in both Dahl et al () and Price and Dahl (), their observed recency effects on evidence integration, like their observed recency effect on evidence evaluation, were only observed when the different pieces of evidence were of strongly opposite valences. Again, the current study includes one piece of evidence that is either incriminating or exonerating and an ambiguous piece of evidence that is not clearly incriminating or exonerating.…”
Section: Presentation Ordermentioning
confidence: 81%
See 4 more Smart Citations
“…Note, however, that in both Dahl et al () and Price and Dahl (), their observed recency effects on evidence integration, like their observed recency effect on evidence evaluation, were only observed when the different pieces of evidence were of strongly opposite valences. Again, the current study includes one piece of evidence that is either incriminating or exonerating and an ambiguous piece of evidence that is not clearly incriminating or exonerating.…”
Section: Presentation Ordermentioning
confidence: 81%
“…However, two recent studies did in fact manipulate the order in which evidence was presented and thus deserve mention. Dahl, Brimacombe, and Lindsay () and Price and Dahl () both presented participant–evaluators with two pieces of evidence (e.g., an alibi and an eyewitness identification decision) in one of two randomly assigned orders and then obtained a number of judgments, including the perceived credibility of the evidence (a measure of evidence evaluation). Results of both studies suggested that when two pieces of sequentially presented evidence have strong, opposite valences, the last piece of evidence is perceived as more credible than it would have been in the absence of the other evidence.…”
Section: Presentation Ordermentioning
confidence: 99%
See 3 more Smart Citations